A new role for muscle segment homeobox genes in mammalian embryonic diapause. Issue 4 (April 2013) - Cha, Jeeyeon; Sun, Xiaofei; Bartos, Amanda; Fenelon, Jane; Lefèvre, Pavine; Daikoku, Takiko; Shaw, Geoff; Maxson, Robert; Murphy, Bruce D.; Renfree, Marilyn B.; Dey, Sudhansu K.
Abstract : Mammalian embryonic diapause is a phenomenon defined by the temporary arrest in blastocyst growth and metabolic activity within the uterus which synchronously becomes quiescent to blastocyst activation and implantation. This reproductive strategy temporally uncouples conception from parturition until environmental or maternal conditions are favourable for the survival of the mother and newborn. The underlying molecular mechanism by which the uterus and embryo temporarily achieve quiescence, maintain blastocyst survival and then resume blastocyst activation with subsequent implantation remains unknown. Here, we show that uterine expression of Msx1 or Msx2, members of an ancient, highly conserved homeobox gene family, persists in three unrelated mammalian species during diapause, followed by rapid downregulation with blastocyst activation and implantation. Mice with uterine inactivation of Msx1 and Msx2 fail to achieve diapause and reactivation. Remarkably, the North American mink and Australian tammar wallaby share similar expression patterns of MSX1 or MSX2 as in mice — it persists during diapause and is rapidly downregulated upon blastocyst activation and implantation. Evidence from mouse studies suggests that the effects of Msx genes in diapause are mediated through Wnt5a, a known transcriptional target of uterine Msx . These studies provide strong evidence that the Msx gene family constitutes a common conserved molecular mediator in the uterus during embryonic diapause to improve female reproductive fitness.